Formulas for Beams with Semi-rigid Connections - Kotlyar, Nathan (Engineering Journal, 1996)
This paper presents practical formulas for beams with semi-rigid connections of variable stiffness, and describes certain limitations for application of these formulas. Using the tables of formulas, the engineer is able to rapidly determine the effect of a partially restrained connection. A practical example illustrates the application of the formulas.